Anti-Analgesic Effect of the Mu/Delta Opioid Receptor Heteromer Revealed by Ligand-Biased Antagonism - Milan-Lobo, Laura (Public Library of Science, 2013)
Delta (DOR) and mu opioid receptors (MOR) can complex as heteromers, conferring functional properties in agonist binding, signaling and trafficking that can differ markedly from their homomeric counterparts. Because of these differences, DOR/MOR heteromers may be a novel therapeutic target in the treatment of pain. However, there are currently no ligands selective for DOR/MOR heteromers, and, consequently, their role in nociception remains unknown. In this study, we used a pharmacological opioid cocktail that selectively activates and stabilizes the DOR/MOR heteromer at the cell surface by blocking its endocytosis to assess its role in antinociception. We found that mice treated chronically with this drug cocktail showed a significant right shift in the ED(50) for opioid-mediated analgesia, while mice treated with a drug that promotes degradation of the heteromer did not. Furthermore, promoting degradation of the DOR/MOR heteromer after the right shift in the ED(50) had occurred, or blocking signal transduction from the stabilized DOR/MOR heteromer, shifted the ED(50) for analgesia back to the left. Taken together, these data suggest an anti-analgesic role for the DOR/MOR heteromer in pain. In conclusion, antagonists selective for DOR/MOR heteromer could provide an avenue for alleviating reduced analgesic response during chronic pain treatment.